2015
DOI: 10.1007/s00259-015-3125-3
|View full text |Cite
|
Sign up to set email alerts
|

Pre-therapeutic dosimetry of normal organs and tissues of 177Lu-PSMA-617 prostate-specific membrane antigen (PSMA) inhibitor in patients with castration-resistant prostate cancer

Abstract: Our first results suggested that (177)Lu-PSMA-617 therapy seems to be a safe method. The dose-limiting organ seems to be the parotid glands rather than kidneys and bone marrow. The lesion radiation doses are within acceptable ranges; however, there is a substantial individual variance so patient dosimetry seems to be mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
139
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(159 citation statements)
references
References 30 publications
14
139
3
3
Order By: Relevance
“…This would allow at least 5 cycles using 7.4 GBq of 177 Lu-PSMA I&T (standard activity at our institution), achieving relevant absorbed doses on tumor lesions and offering the possibility of several cycles for midterm tumor control. These findings are in line with data presented by Kabaskal et al using pretherapeutic dosimetry for 177 Lu-PSMA-DKFZ-617 and who calculated a maximum activity of 30 GBq to achieve a 23-Gy kidney dose (13). Nevertheless, these absorbed dose limits are based on the conventionally fractionated external-beam therapy and cannot necessarily be directly applied to low-dose-rate radiation (28).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This would allow at least 5 cycles using 7.4 GBq of 177 Lu-PSMA I&T (standard activity at our institution), achieving relevant absorbed doses on tumor lesions and offering the possibility of several cycles for midterm tumor control. These findings are in line with data presented by Kabaskal et al using pretherapeutic dosimetry for 177 Lu-PSMA-DKFZ-617 and who calculated a maximum activity of 30 GBq to achieve a 23-Gy kidney dose (13). Nevertheless, these absorbed dose limits are based on the conventionally fractionated external-beam therapy and cannot necessarily be directly applied to low-dose-rate radiation (28).…”
Section: Discussionsupporting
confidence: 73%
“…Beside the high and specific uptake of PSMA ligands in PC tissue, different normal organs (e.g., kidney, salivary glands, proximal intestine) exhibit tracer accumulation. Recently published studies using the theranostic DOTA-conjugated PSMA ligand 177 Lu-PSMA-DKFZ-617 reported results for both posttherapeutic dosimetry (9,11,12) and pretherapeutic dosimetry (13).…”
mentioning
confidence: 99%
“…0.03 Gy/GBq) and kidneys (approx. 0.6 Gy/GBq) should be considered as dose limiting organs (6)(7)(8)18,19). (14) and despite moderate xerostomia there is no evidence of relevant treatment-related toxicity.…”
Section: Responsementioning
confidence: 99%
“…Coupling with DOTA enables labeling with several diagnostic and therapeutic radionuclides (5). Different centers (6)(7)(8) reported favorable dosimetry for 177 Lu-PSMA-617, which in regard to kidney (approx. 0.6 Gy/GBq) and red marrow dose (approx.…”
Section: Introductionmentioning
confidence: 99%
“…The structural key element of PSMA-617 is its linker design, which triggers binding and internalization of the substance through a presumed interaction of the rigid (tranexamic acid) and aromatic (2-naphthylalanine) amino acids with rigid parts of the PSMA binding pocket (6). Although prospective clinical trials are still pending, the 177 Lu-and 225 Ac-labeled versions of this PSMA inhibitor have already proved its therapeutic potential (7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%